PENGARUH KOMUNIKASI, DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEGAWAI - Balthasar Watunglawar; Katarina Leba (LPPM Politeknik Saint Paul Sorong, 2020)
The purpose of this paper is to describe and analyze the influence of communication, discipline, and motivation on employee performance. To achieve these objectives, this study uses quantitative research methods. Data were collected through questionnaires and documentation of 38 respondents in the office of Badan Kepegawaian, Pendidikan dan Pelatihan Kabupaten Teluk Wondama analyzed using SPSS 22. The results showed that there was a significant influence between communication, discipline, and motivation on employee performance. So to improve employee performance, the organization and institutional management must pay attention to improving good communication, discipline, and motivation. The findings of this study are expected to be useful for further researchers in the fields of management, accounting, administration and economics.